PEDAGOGICAL CONTENT KNOWLEDGE (PCK) INTEGRATED ISLAMIC FOR STUDENTS OF FTK UIN SULTHAN THAHA SAIFUDDIN JAMBI - Ilyas Idris; Mardalina -; Louisiana Muliawati; Chandri - (INNOVATIO: Journal for Religious Innovations Studies, 2023)
Pedagogical competence was a competency that must be possessed by educators to master material and principles in the learning process. In addition, teachers are required to be able to implement the curriculum in their learning. Teachers must also be able to create learning activities that can educate their students so that they are able to develop the potential of their students. The last competency that a teacher must have communication skills, namely communicating with students, assessing and evaluating their learning. These three types of pedagogical competencies must be mastered by an educator or prospective student educator of FTK UIN Sulthan Thaha Saifuddin Jambi who had PCK Islamic integrated abilities ranging from good to very good. The value of the 8 indicators of student PCK Islamic integrated ranges from 71% to 100%. Abstrak: Kompetensi pedagogik merupakan kompetensi yang harus dimiliki seorang pendidik untuk menguasai materi dan prinsip dalam proses pembelajaran. Selain itu, guru dituntut untuk mampu mengimplementasikan kurikulum dalam pembelajarannya. Guru juga harus mampu menciptakan kegiatan pembelajaran yang dapat mencerdaskan anak didiknya sehingga mampu mengembangkan potensi anak didiknya. Kompetensi terakhir yang harus dimiliki oleh seorang guru adalah kemampuan komunikasi, yaitu berkomunikasi dengan siswa, menilai dan mengevaluasi pembelajarannya. Ketiga jenis kompetensi pedagogik tersebut harus dikuasai oleh seorang pendidik atau calon pendidik mahasiswa FTK UIN Sulthan Thaha Saifuddin Jambi yang memiliki kemampuan PCK Islami terpadu mulai dari baik sampai sangat baik. Nilai dari 8 indikator PCK Islam siswa terpadu berkisar antara 71% sampai dengan 100%. Kata kunci: PCK, Islamic integrated, FTK UIN Sulthan Thaha Saifudin Jambi